The Application of Semi-Fowler Position to Oxygen Saturation in Chronic Kidney Disease Patients - Inesta, Indi; Karlina, Nonok; Muadi, Muadi (Jurnal Keperawatan Profesional, 2025)
Chronic Kidney Disease (CKD) is a decline in kidney function that occurs gradually over a long period of time and will get worse over time. One of the clinical symptoms of CKD is shortness of breath which is a lack of oxygen entering the lungs. Sem-fowler position as one of the nursing actions that can reduce shortness of breath so that oxygen intake increases and shortness of breath decreases. This study aims to analyze nursing care by giving sem-fowler position to CKD patients with nursing problems of gas exchange disorders. This research method uses a case study method conducted from January 30 - February 01, 2025. The subject in this scientific work involves 1 patient with CKD cases.  Data collection using interview techniques, observation, and physical examination. Implementation carried out for 3 consecutive days, accompanied by measurement of peripheral capillary oxygen saturation (SpO2) using a Mindray PM 60 Oxymeter. The characteristics of this case study patient are a 61-year-old female patient and experiencing end-stage CKD (Stage V). Based on the results of oxygen saturation values before application with a value of 94% and after application including the normal category with a value of 98%. The conclusion of the application of the semi-fowler position is able to increase oxygen saturation in CKD patients.